SIKAP MASYARAKAT TERHADAP PENGELOLAAN HUTAN DESA KAJULANGKO KECAMATAN AMPANA TETE KABUPATEN TOJO UNA-UNA - Jasa, Jafar Arb.; Umar, Syukur; Pribadi, Hendra; Anwar, Anwar (Universitas Tadulako, 2020)
Community forest is basically a state forest, managed by the society trough a rural administrative organization, and used for the welfare the villager. Village forest management can be seen from the distribution arrangements of manage land to any farmer. Village ordinances are regulated that each village of farmers are only allowed to manage the maximum forest land of 0.5 hectares for farmers based on historical background who managed more than 0.5 hectares before being designated as community forest. The forest of Kajulangko is located in the village of villagesÂ covering the sub-district of Tojo Una-Una. Where the population of the Kajulangko village was 1129, the number of family heads at the time of the formation of the Kajulangko village was 278 family heads. The village area of Kajulangko is approximately 12 square kilometers. To understand the attitude of society can be analyzed using descriptive methods he or she USES a scale of 1-2-3-4-5. Studies have shown that peopleâ€™s attitude toward community forest is good for the society being high (119), good community forest for the village government is likely to be moderate (62), village forest is important for the moderateeconomic welfare (57) and village forests are essential for forest sustainability to be very high (135).Keywords: Community forest, management, community attitude